Why are children absent from preschool? A nationally representative analysis of Head Start programs - Purtell, Kelly M.; Ansari, Arya (Frontiers in Education, 2022)
Introduction Children who are absent from school, including preschool, do not make the same academic gains as their non-absent peers. However, we know little about what predicts absenteeism among preschool-attending children. Methods We used the Family and Child Experiences Study - 2009, a nationally representative sample of Head Start attendees (n = 2,842), to test the associations between a comprehensive set of child, family, and center factors, and children’s levels of absenteeism across the preschool year. Results Our findings highlight the multi-faceted nature of absenteeism. Family necessity, family routines, and center-level characteristics were all associated with absenteeism. Discussion Reducing preschool absenteeism requires a comprehensive approach as the factors that shape absences are varied. Our findings suggest that center-level strategies focused on outreach and classroom quality are important future directions.